Breast Cancer–Related Lymphedema: Quality of Life after Lymph Node Transfer. Issue 6 (June 2016) - De Brucker, Ben; Zeltzer, Assaf; Seidenstuecker, Katrin; Hendrickx, Benoit; Adriaenssens, Nele; Hamdi, Moustapha
Abstract : Background: Breast cancer–related lymphedema affects multiple aspects of patients' daily lives. The main aim of this study was to assess the impact of vascularized lymph node transfer on the quality of life in patients with lymphedema. Methods: Between 2007 and 2012, 25 female patients with breast cancer–related lymphedema underwent vascularized lymph node transfer. In 22 cases, the patients underwent a simultaneous deep inferior epigastric artery perforator flap breast reconstruction based on the superficial circumflex iliac artery. The influence on quality of life was evaluated using the Upper Limb Lymphedema-27 questionnaire, which includes physical, psychological, and social dimensions. The authors also investigated risk factors for lymphedema, such as body mass index, smoking, age, and time between start of lymphedema and vascularized lymph node transfer, and their impact on quality of life. Results: Twenty-one patients (84 percent) had an improvement of quality of life after vascularized lymph node transfer. The mean physical, psychological, and social scores were significantly improved postoperatively ( p < 0.001). Risk factors for the development of lymphedema did not influence quality of life among patients with breast cancer–related lymphedema. Skin infections disappeared in 50 percent of the cases. Eleven patients (44 percent) discontinued compression therapy at a mean postoperative time interval of 29 months (range, 8 to 64 months). In the other patients (56 percent), the average frequency of compression therapy decreased from three sessions to one session per week. Conclusion: Vascularized lymph node transfer significantly improves quality of life among patients with breast cancer–related lymphedema. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.